Results of the preliminary survey on the avifauna in the Xuanson national park (Phutho province) by the mist-nets method - Hung Son, Nguyen Lan; Van, Nguyen Thanh (Academia Journal of Biology, 2014)
Using the mist-nets method to study the avifauna in the Xuanson national park (Phutho province) during January and March of 2006, we have captured, at three research camps on the Ten mountain (1.253 m/alt.), 311 birds belonging to 46 species of 11 families, 4 orders. Passeriformes was the most abundant order of families (7 families) and species (40 species). Among these 11 families, Sylvidae was the most abundant one of species (17 species). Among these 311 captured birds, 284 birds were ringed and 40 ones were recaptured. During the two bird survey times in the Xuanson national park, Alcippe morrisonia was captured and recaptured most frequently. Based on the mean similarity dendrogram, the bird species composition was similar between the camp 2 and the camp 3 and different from the camp 1. The bird capture by mist-nets could give us an insight into the health and the demography of the studied bird population. To estimate the evolution trends and the health status of the birds community in Xuanson national park, it was necessary to continue this study for a long period.